Field Performance and Genetic Fidelity of Selected Cocoa (Theobroma cacao L.) Clones Regenerated Through Somatic Embryogenesis - Gibson, Entuni (Universiti Malaysia Sarawak (UNIMAS), 2021)
Somatic embryogenesis is a type of propagation that has a great potential to accelerate the production of elite planting material in many commercial crops. However, evaluation on the field performance, morphological characteristics, flower reproduction structure, Vascular Streak Dieback (VSD) disease and genetic fidelity of the regenerated plant should be assessed especially in a long living fruit crop species such as cocoa. Thus, the series of evaluations were conducted in the present study to evaluate the qualities of the four elite cocoa clones (MCBC1, PBC230, KKM22 and KKM4) regenerated from staminode culture, immature zygotic embryo culture and grafting as a control. The MCBC1, PBC230 and KKM22 clones were morphologically and physically identical to conventional grafted clones after 24 months from transplanting based on the parameters under studied. Nevertheless, only MCBC1 had the faster growth with a stem diameter of 60.1 mm and stem height of 1.19 m, while PBC230 and KKM22 had 57.3 mm in stem diameter and 1.10 m in height, at 24 months after transplanting. Further field screening indicated that the MCBC1 clone was resistant compared to other by showing the least disease severity scores (1.98) and superior recovery by faster growth of new shoots after pruning of the infected twig (±150 mm). The MCBC1 clone also had the lowest stomata number (abaxial = 27 and adaxial = 26) and smallest stomatal pore area (10.9 μm2). The abaxial leaf of MCBC1 had the fewest number of opened stomata (16 stomata/FOV). The stomata feature in the MCBC1 clone is crucial for leaf structural defence against the penetration of Oncobasidium theobromae fungi which responsible for the disease. The off-type progenies found only in the KKM4 clone from immature zygotic embryo culture suggested the influence of cocoa genotype and micropropagation type for the somatic embryogenesis culture. This clone which was prone to variation and after propagated from immature zygotic embryo culture produced the iv maximum up to five jorquette branches, shortest jorquette length (0.99 m) and leaf blade length (236.4 mm) as well as smaller individual leaf area (237.1 cm2) than other clones. The higher number of four flat beans per fruits and lowest individual seed fresh weight (4.13 g) has led to the lightest fruit fresh weight in KKM4 clone of immature zygotic embryo culture (339.6 g). This is contrasted with the KKM4 clone from staminode culture and grafting with the fresh fruit weight averaged 404.0 g. Additionally, the KKM4 variants produced the shortest seed length (21.2 mm) and width (11.5 mm) compared with the KKM4 clone of staminode culture and grafting with an average seed length of 22.4 mm and seed width of 12.4 mm. The shortest staminode to style distance in KKM4 clone variants during wet (1.85 mm) and dry seasons (1.80 mm) has reduced the flower pollination efficiency by insect. Final validation via molecular analysis using SSR primers demonstrated the DNA variations in KKM4 clone regenerated from immature zygotic embryo culture. Around twelve SSR primers including mTcCIR37, mTcCIR7, mTcCIR60, mTcCIR6, mTcCIR33, mTcCIR11, mTcCIR8, mTcCIR18, mTcCIR1, mTcCIR40, mTcCIR22 and mTcCIR26 successfully detected variation in the allelic profiles of KKM4 from immature zygotic embryo culture compared with grafted donor clones. These SSR primers which were polymorphic and amplified about 316 alleles with size averaged 127.03 bp to 347.22 bp. Through this study, somatic embryogenesis culture particularly staminode culture is a great alternative for commercial propagation of superior cocoa clones of high yield potential and resistance to pest and diseases such as MCBC1, PBC230, KKM4 and KKM22 clones in Malaysia. Nevertheless, for KKM4 clone, the protocols and culture for the immature zygotic embryo culture need to be optimized.